Advances in family-based interventions in the neonatal ICU. Issue 2 (April 2016) - Welch, Martha G.; Myers, Michael M.
Abstract : Purpose of review: Despite advances in medical care, preterm infants remain at risk for many adverse outcomes. This article reviews findings from several recent neonatal ICU (NICU) interventions and a trial of a novel nurture-based approach, Family Nurture Intervention (FNI). Recent findings: Recent trials reviewed here find positive effects of a variety of family-related interventions focused on parental guidance. These interventions target prescribed physical activities with infants, parents' stress, and the parents' ability to recognize their positive and negative behaviors with their infants. Beneficial effects include reductions in parenting stress, maternal anxiety, and depression. A different approach, FNI, is aimed at establishing mother–infant emotional connection. As in other trials, FNI also decreased maternal symptoms of anxiety and depression, and increased maternal sensitivity. Additionally, FNI led to positive short and long-term effects on infant neurobehavioral outcomes at term and 18 months. Summary: A number of recent parent-based NICU interventions have been effective at reducing preterm parent stress. Another, FNI, has positive effects on both maternal and infant outcomes and promises to be cost-effective. Future decreases in long-term morbidity in preterm infants will increasingly rely on nonmedical interventions. Therefore, the rigorous development and testing of such interventions should be a high priority in perinatology research.